Two complementary model-based methods for calculating the risk of international spreading of a novel virus from the outbreak epicentre : the case of COVID-19 - Massad, Eduardo; Amaku, Marcos; Wilder-Smith, Annelies; Santos, Paulo Cesar Costa dos; Struchiner, Claudio Jose; Coutinho, Francisco Antonio Bezerra (Epidemiology and infection, 2020)
We present two complementary model-based methods for calculating the risk of international spread of the novel coronavirus SARS-CoV-2 from the outbreak epicentre. One model aims to calculate the number of cases that would be exported from an endemic country to disease-free regions by travellers. The second model calculates the probability that an infected traveller will generate at least one secondary autochthonous case in the visited country. Although this paper focuses on the data from China, our methods can be adapted to calculate the risk of importation and subsequent outbreaks. We found an average R0 = 5.31 (ranging from 4.08 to 7.91) and a risk of spreading of 0.75 latent individuals per 1000 travellers. In addition, one infective traveller would be able to generate at least one secondary autochthonous case in the visited country with a probability of 23%.